Diagnostic decision-making, vertebral augmentation, and osteoporosis therapy in vertebral compression fractures: a narrative review - Garcia Annette Findlay; Mark Ehioghae; Lancelot Benn; Alejandro Perez Albela; Theodore Quan; Bryce Alexander Basques; Aviram M. Giladi; Kevin Yoon; Jonathan Paul Japa; Abdi Khalif; Addisu Mesfin (Asian Spine Journal, 2026)
Vertebral compression fractures (VCFs) represent the most prevalent osteoporotic fracture and constitute a growing cause of morbidity, mortality, and healthcare utilization worldwide. Although often considered benign, VCFs are associated with chronic pain, progressive spinal deformity, functional impairment, decreased pulmonary capacity, and increased short- and long-term mortality, especially in older adults. Despite their high prevalence, key challenges persist regarding appropriate diagnostic evaluation, optimal treatment selection, and integration of osteoporosis management following fracture. This narrative review consolidates current evidence on the epidemiology, pathophysiology, diagnostic evaluation, management strategies, and public health implications of VCFs, with a focus on emerging spine-focused care models. VCFs predominantly result from compromised vertebral strength secondary to osteoporosis-related deterioration of trabecular microarchitecture, although traumatic and pathologic etiologies should also be considered. Diagnosis involves careful clinical assessment combined with imaging, with magnetic resonance imaging serving as a key modality for distinguishing acute fractures from chronic deformities or malignancy. Despite advances in diagnostic techniques, VCFs remain underrecognized and undertreated, contributing to avoidable disability and recurrent fractures. This narrative review synthesizes contemporary evidence, highlighting practical considerations for clinical decisionmaking in VCF care. Particular emphasis is placed on differentiating acute symptomatic fractures from chronic deformities or pathologic collapse, identifying patients most likely to benefit from vertebral augmentation, and defining surgical indications in the setting of neurologic compromise, instability, or progressive deformity. Conservative management, incorporating analgesia, early mobilization, and rehabilitation, remains the first-line approach for most stable fractures. Vertebroplasty and balloon kyphoplasty may provide short-term pain relief in carefully selected patients with persistent symptoms. However, the long-term benefits of augmentation and optimal patient selection criteria remain under investigation. Treatment options range from conservative measures—including analgesia, bracing, mobilization, rehabilitation, and osteoporosis-directed pharmacotherapy—to minimally invasive vertebral augmentation procedures such as vertebroplasty and balloon kyphoplasty. Vertebral augmentation may provide short-term improvements in pain and function in appropriately selected patients, although its long-term benefits and optimal indications remain under investigation. Surgical decompression and stabilization are reserved for patients with neurological compromise, instability, or progressive deformity. From a public health perspective, deficiencies in osteoporosis screening, delayed diagnosis, and disparities in treatment access continue to affect diverse socioeconomic and racial groups. Emerging innovations, including fracture liaison services, risk stratification tools such as FRAX, and artificial intelligence–based predictive models, may enhance early detection and personalized care. VCFs represent sentinel manifestations of systemic skeletal fragility that warrant evaluation of underlying osteoporosis and implementation of secondary fracture prevention. Pharmacologic therapies, including antiresorptive and anabolic agents, play a key role in reducing recurrent fracture risk, although treatment selection should be individualized. Multidisciplinary, patient-centered strategies focused on early diagnosis, prevention, equitable care delivery, and standardized management are essential to address the growing global burden of VCFs. A structured, patient-centered approach to diagnosis, treatment selection, and post-fracture care may enhance outcomes and reduce the long-term burden associated with VCFs.